Functional study of potential sHSPs in Arabidopsis and tomato under environmental stress. - Escobar, Mariela Raquel (2019)
Small heat shock proteins (sHSPs) respond to many environmental stresses, stabilizing early unfolding protein intermediates and avoiding their irreversible aggregation. In plants, organellar sHSPs are a unique cellular feature. The primary structure of sHSPs includes a N-terminal sequence of variable sequence and length, a conserved domain known as α-crystallin domain (ACD) and a non-conserved C-terminal sequence. The ACD represents the conserved characteristic present in all sHSPs, although there are other proteins that contain an ACD but are not sHSPs. sHSPs belong to a big superfamily, and the functional and physiological relevance of the different sHSPs remains largely unknown. The objective of this study was to understand the role of mitochondrial sHSPs in Arabidopsis thaliana and Solanum lycopersicum under environmental stresses and to characterize putative bidirectional promoters driving the expression of ACD proteins with head-to-head orientation. This work covers aspects from the genomic organization and function of sHSPs-M in Arabidopsis to the role of sHSPs-M in chilling stress of tomato fruit. To perform all the experiments, Arabidopsis and tomato mutants using artificial microRNA technology were generated and analyzed in their proteome, metabolome, and lipidome. In the first part of this work, the functional characterization of head-to-head oriented genes encoding ACD proteins and the correspondent intergenic regions was performed. Four different bidirectional promoters in the A. thaliana genome, including the one of At5g51440 that encodes a mitochondrial sHSP (sHSP23.5), were successfully identified and characterized. The data suggest that the bidirectional promoter contained in the pair At5g51430-At5g51440 is strongly heat induced in one direction but not in the other. The promoter of At1g06460-At1g06470 showed comparable high activity in both directions and thus has a great potential to be used in genetic engineering. The other two promoters showed greater strength in one side and can be considered as asymmetric bidirectional promoters. This functional study of the promoters revealed the biotechnological potential of them because they can be induced specifically in a certain condition (such as high temperature) in one or two directions when it is required. In the second part, functional characterization of the mitochondrial sHSPs under stress conditions and during A. thaliana development is presented. Three gene paralogues were found in Arabidopsis (At5g51440, At4g25200, and At1g52560), and artificial microRNA were used to generate knock-down mutants (single, double and triple amiR). The single and double amiRs (for sHSP23.5 and sHSP23.6) did not show evidently affected phenotype, probably because of functional compensation or redundancy of the mitochondrial sHSPs. On the other hand, the triple amiR23.5/23.6/26.5 mutants showed an altered phenotype in the vegetative and reproductive stages. They have reduced leaves areas, but not number of epidermal cells per leaf, chlorotic leaves, shorter root, and reduced seed yield when compared to Col-0 plants. Plants of triple amiR were considerably small due to the alteration in the process of cell expansion but not in the cellular proliferation, which indicates a profound alteration in the plant developmental program. Proteomic analysis of the amiR mutants revealed significant upregulation of various metabolism-related proteins and alterations in the abundance of several proteins that are involved in translation and in the ribosome functioning and structure. Triple amiR mutant exhibited a higher number of proteins with differential abundance related to these processes compared to the other single and double amiR23.5/23.6 mutants. Such a wide change in ribosome-related proteins suggests a possible alteration in the proper ribosome function. The data exposed in this work provide evidence of the important roles that sHSPs-M may play, not only in the heat response but also in the plant development of Arabidopsis. Results demonstrate that a functional compensation might be responsible for the phenotype in mutants lacking single sHSPs-M. However, the reduction of the three sHSPs-M caused a profound disruption in the mitochondria and ribosome functionality that severely affected the energy metabolism and the overall cell homeostasis, leading to alterations in the correct plant development. In the last part of this work, the functional consequences of the down-regulation of sHSP23.8 in tomato fruit were investigated and analyzed in their phenotype and in their susceptibility to chilling injury. Pre-chilled fruit of amiR23.8 mutant showed higher loss of water and increased ion leakage of pericarp tissue compared to WT fruit. The amiR23.8 fruit deterioration indicates that it is highly susceptible to cold stress and developed chilling injury symptoms. The lipidome of fruit after chilling of amiR23.8 showed altered amounts of glycerolipids, and the level of saturated lipids in amiR23.8 decreased, but not lower than the level in WT under normal conditions. The opposite was found in the relative percentage of unsaturated lipids, having amiR23.8 fruit significantly lower levels in normal conditions and after chilling. The results presented here indicate a differential degradation of extraplastidic and plastidic lipids in amiR23.8 fruit, and alterations in the remodeling of the lipidome after cold stress, which may lead to higher sensitivity to chilling injury. The results discussed here indicate that sHSP23.8 may play an important role in the protection mechanisms against chilling stress in tomato fruit.